2012
DOI: 10.1186/1472-6920-12-26
|View full text |Cite
|
Sign up to set email alerts
|

Peer observation of teaching as a faculty development tool

Abstract: BackgroundPeer observation of Teaching involves observers providing descriptive feedback to their peers on learning and teaching practice as a means to improve quality of teaching. This study employed and assessed peer observation as a constructive, developmental process for members of a Pediatric Teaching Faculty.MethodsThis study describes how peer observation was implemented as part of a teaching faculty development program and how it was perceived by teachers. The PoT process was divided into 4 stages: pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 14 publications
6
81
1
4
Order By: Relevance
“…While student evaluations are the most common form of teaching assessment in pharmacy schools, peer review of teaching has become widespread and offers many benefits such as the promotion of more reflective teaching practices. 1,4,9 Our peer review of teaching program involved single classroom observations performed by one of a three-member peer review team, similar in scope to the program described by Sullivan et al, followed by feedback provided through a standardized tool that included rating scales and written comments, similar to the template described by Davis and domains described by Wellein et al 6,7,11 Our evaluation of the impact of our peer review program on teaching practices and perception identified three key findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While student evaluations are the most common form of teaching assessment in pharmacy schools, peer review of teaching has become widespread and offers many benefits such as the promotion of more reflective teaching practices. 1,4,9 Our peer review of teaching program involved single classroom observations performed by one of a three-member peer review team, similar in scope to the program described by Sullivan et al, followed by feedback provided through a standardized tool that included rating scales and written comments, similar to the template described by Davis and domains described by Wellein et al 6,7,11 Our evaluation of the impact of our peer review program on teaching practices and perception identified three key findings.…”
Section: Discussionmentioning
confidence: 97%
“…9 Many models have emerged for peer review of teaching. 2,3,5,6,7,9,10,11,12,13,14,15,16,17,18,19,20 The following variations are all described in the literature: classroom observation alone (may be a single visit or multiple visits), or a more comprehensive review of materials including student work, assessment, and syllabi; feedback tools may include simple checklists, rating scales, written feedback, and/or verbal feedback; reviewers may or may not receive specialized training; reviewers may consist of a small group of individuals chosen for the task or pairs that agree or are selected to conduct reciprocal reviews; and pre-and/or post-observation meetings may be included. Given this variation, it is not clear that benefits attributed to peer review are generalizable in all contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers mentioned that by peer observed teaching, they were able to make useful changes that led to improvements in overall session, improved audio visual skills, and resulted in more effective teaching experience for the students. 3 Roermund et al, 2013 in a similar study reported that teachers who had positive feedback from their residents showed positive attitude towards their residents and self-confidence about their teaching abilities. Whereas, teachers with poor results tended to discuss the items and tried to relate the results caused outside themselves and mentioned that the residents didn't understand their approach or attributed the outcomes to the characteristics of residents.…”
mentioning
confidence: 99%
“…2 Peer observed teaching provides an opportunity to respond to their peers in teaching learning practice, which improves and accounts for the quality teaching in higher education. 3 Ramsden, 2003 has described that there has been no single right answer to the problem of improving the quality of University teaching. 4 Shortland, 2004 has stated that the choice of inappropriate methodology may lead to de-motivating feedback, which may present a dilemma in observation practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation